Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Let's solve the given mathematical expression step-by-step:
We are given the expression [tex]\(\left(\frac{x^{-2}}{y^2}\right)^{\frac{1}{2}}\)[/tex] with [tex]\(x = -3\)[/tex] and [tex]\(y = 2\)[/tex].
1. Evaluate [tex]\(x^{-2}\)[/tex]:
Since [tex]\(x = -3\)[/tex],
[tex]\[ x^{-2} = (-3)^{-2} \][/tex]
The exponent [tex]\(-2\)[/tex] means taking the reciprocal of [tex]\((-3)\)[/tex] squared:
[tex]\[ (-3)^{-2} = \frac{1}{(-3)^2} = \frac{1}{9} \][/tex]
2. Evaluate [tex]\(y^2\)[/tex]:
Since [tex]\(y = 2\)[/tex],
[tex]\[ y^2 = 2^2 = 4 \][/tex]
3. Form the fraction [tex]\(\frac{x^{-2}}{y^2}\)[/tex]:
Substitute the values we found into the fraction:
[tex]\[ \frac{x^{-2}}{y^2} = \frac{\frac{1}{9}}{4} \][/tex]
4. Simplify the fraction:
Dividing [tex]\(\frac{1}{9}\)[/tex] by [tex]\(4\)[/tex] is the same as multiplying [tex]\(\frac{1}{9}\)[/tex] by the reciprocal of [tex]\(4\)[/tex]:
[tex]\[ \frac{\frac{1}{9}}{4} = \frac{1}{9} \times \frac{1}{4} = \frac{1}{36} \][/tex]
5. Apply the exponent [tex]\(\frac{1}{2}\)[/tex]:
Now we need to take the square root of [tex]\(\frac{1}{36}\)[/tex] because raising to the power of [tex]\(\frac{1}{2}\)[/tex] is the same as taking the square root:
[tex]\[ \left(\frac{1}{36}\right)^{\frac{1}{2}} = \sqrt{\frac{1}{36}} \][/tex]
6. Find the square root of [tex]\(\frac{1}{36}\)[/tex]:
[tex]\[ \sqrt{\frac{1}{36}} = \frac{1}{\sqrt{36}} = \frac{1}{6} \][/tex]
So, the final answer is:
[tex]\[ \left(\frac{x^{-2}}{y^2}\right)^{\frac{1}{2}} = \frac{1}{6} \approx 0.16666666666666666 \][/tex]
We are given the expression [tex]\(\left(\frac{x^{-2}}{y^2}\right)^{\frac{1}{2}}\)[/tex] with [tex]\(x = -3\)[/tex] and [tex]\(y = 2\)[/tex].
1. Evaluate [tex]\(x^{-2}\)[/tex]:
Since [tex]\(x = -3\)[/tex],
[tex]\[ x^{-2} = (-3)^{-2} \][/tex]
The exponent [tex]\(-2\)[/tex] means taking the reciprocal of [tex]\((-3)\)[/tex] squared:
[tex]\[ (-3)^{-2} = \frac{1}{(-3)^2} = \frac{1}{9} \][/tex]
2. Evaluate [tex]\(y^2\)[/tex]:
Since [tex]\(y = 2\)[/tex],
[tex]\[ y^2 = 2^2 = 4 \][/tex]
3. Form the fraction [tex]\(\frac{x^{-2}}{y^2}\)[/tex]:
Substitute the values we found into the fraction:
[tex]\[ \frac{x^{-2}}{y^2} = \frac{\frac{1}{9}}{4} \][/tex]
4. Simplify the fraction:
Dividing [tex]\(\frac{1}{9}\)[/tex] by [tex]\(4\)[/tex] is the same as multiplying [tex]\(\frac{1}{9}\)[/tex] by the reciprocal of [tex]\(4\)[/tex]:
[tex]\[ \frac{\frac{1}{9}}{4} = \frac{1}{9} \times \frac{1}{4} = \frac{1}{36} \][/tex]
5. Apply the exponent [tex]\(\frac{1}{2}\)[/tex]:
Now we need to take the square root of [tex]\(\frac{1}{36}\)[/tex] because raising to the power of [tex]\(\frac{1}{2}\)[/tex] is the same as taking the square root:
[tex]\[ \left(\frac{1}{36}\right)^{\frac{1}{2}} = \sqrt{\frac{1}{36}} \][/tex]
6. Find the square root of [tex]\(\frac{1}{36}\)[/tex]:
[tex]\[ \sqrt{\frac{1}{36}} = \frac{1}{\sqrt{36}} = \frac{1}{6} \][/tex]
So, the final answer is:
[tex]\[ \left(\frac{x^{-2}}{y^2}\right)^{\frac{1}{2}} = \frac{1}{6} \approx 0.16666666666666666 \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.